Strategi Pengembangan Agribisnis Nanas Tangkit Desa Tangkit Baru Kecamatan Sungai Gelam Kabupaten Muaro Jambi - Haris, Muhamad; Alamsyah, Zulkifli; Yanita, Mirawati (Universitas Batangahari Jambi, 2025)
The research was conducted in Tangkit Baru Village as the main center of pineapple production in Jambi Province. This study aims to: 1) Describe the general description of pineapple tangkit agribusiness in Tangkit Baru Village, Sungai Gelam District, Muaro Jambi Regency, 2) Identify strategic environmental conditions in the development of pineapple tangkit agribusiness in Tangkit Baru Village, Sungai Gelam District, Muaro Jambi Regency, 3) Formulate a strategy for developing pineapple tangkit agribusiness in Tangkit Baru Village, Sungai Gelam District, Muaro Jambi Regency. The sampling method in this study was carried out purposively (deliberately) to 28 key informants and 7 key experts. The data used are primary and secondary data. The data were analyzed by descriptive methods, SWOT analysis (Strenght, Weakness, Oppoturnities, Threats) and AHP (Analytical Hierarchy Process) analysis. This research will be conducted from December 27, 2023, to February 27, 2024. The results showed: 1) Pineapple agribusiness consists of 5 sub-systems, namely the procurement and distribution subsystem of production facilities (saprodi), the on-farm subsystem or agricultural production, the processing subsystem of marketing subsystems and supporting subsystems (institutional); 2) Identification of the strategic environment includes internal factors consisting of 7 strengths and 11 camps, while external factors consist of 7 opportunities and 6 threats; 3) The results of the SWOT analysis show that the development of pineapple agribusiness is in quadrant I (aggressive strategy) with several alternative strategies that can be done including: increasing production by maximizing authorized capital (natural resources and human resources), STA development and expanding market share. The results of the AHP analysis show that the development of STA is the most important alternative in the development of tangkit pineapple agribusiness because the existence of STA will be able to explore all the potential strengths possessed in the development of tangkit pineapple agribusiness.